Fluid boundaries in 'The Awntyrs off Arthure' and 'Sir Isumbras' - Richmond, Andrew (Open Library of Humanities, 2018)
Encounters with water shape the Middle English romances of The Awntyrs off Arthure and Sir Isumbras. In the latter, rivers and the 'Greek Sea' serve to distinguish separate sections of the narrative: the river marks the point at which the titular hero's family unit begins to break down, while the beach of the sea marks the lowest point of his social power. Yet his later traversal of the Greek Sea itself allows him to reassemble his family and reclaim his aristocratic power. In Awntyrs, the Tarn Wathelene (or Wadling) ties the actions of the romance's first episode onto a specific spot in the real-world English landscape, while connecting the text to a number of other Arthurian romances that also mention or take place near the tarn. This article, then, argues that the waterscapes in these two texts illustrate a late-medieval understanding of tarns, rivers, and seas as explicitly alien, yet intimately physical embodiments of divine power in the natural world. Taken together, these poems-one a metrical romance, the other alliterative-show how interests in waterscapes crossed boundaries within the muddy genre of romance itself, and reveal that water upsets such human categories as family and property. Tarns, rivers, and seas turn human bodies, instead, into their possessions; the disturbing experience of that dehumanizing process should, these texts imply, wear the world, its history, and its bonds away, until even the greatest knights or ladies are left alone with watery forms beyond the pale of human understanding. © 2018 The Author(s).
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-894-901-510-053, pop00161
Keywords: dept.eng; peer-reviewed

Landscape in Middle English Romance: The Medieval Imagination and the Natural World - Richmond, Andrew M. (Cambridge University Press, 2021)
"In Sir Isumbras, one of the most enduringly popular late medieval romances, the penitential experience of its eponymous hero (modeled off of the evergreen St. Eustace tales) is grounded in a careful exploration of hillside ironmines and the communities of smiths that rely upon them. Such an interest in natural resource management and industrial development derives from the notable focus on charting topography that distinguishes the central third of the romance - marking Isumbras's transition from secular to divine systems of values, and his geographical movement from Christian to Saracen lands. Similarly, in the fourteenth-century Middle English version of William of Palerne (hereafter William), the eponymous protagonist flees with his lover, Melior, through a world of forests and bays that overflows with topographical details. These intricate explanations of quarry pits, hollow oaks, roadside groves, seaside caves, and war-torn estates together compose a perspective on landscape defined by networks of economic exchange. In this regard, the predominant view of the natural world presented in William ties it to earlier romances such as Havelok the Dane, a text interested in the systems of exchange that knit seaside fishermen to urban markets; and to later texts such as the Middle English versions of Partonope of Blois, which demonstrates in its depictions of estates the mercantile and agricultural uses of natural spaces that underlie the successful maintenance of a noble identity. This chapter, then, will discuss how Middle English romances' attention to the management and harvest of natural resources often reveals the link between country and urban spaces created by the exchange of such goods. I will also consider how sympathetic portrayals of laborers and other low-class harvesters of natural resources suggest that romances, particularly around the turn of the fifteenth century, reflect the shifting nature of their bourgeois-gentry audience by engaging with the environmental experiences of merchants, household clerks, reeves, franklins, and gentry farmers in addition to those of the higher aristocracy"–
SCSU Faculty Scholar Award
Keywords: History and criticism; English literature; History and criticism; Landscapes in literature; Seashore in literature; Middle English; 1100-1500; Romances; English; SCSU Faculty Scholar Award; award_winner; dept.eng

Environmental description and social elevation in Torrent of Portyngale - Richmond, Andrew M. (JEGP, Journal of English and Germanic Philology, 2023)
0 citations (Crossref) [2023-10-31]
Keywords: dept.eng; peer-reviewed

“The broken schippus he ther fonde”: Shipwrecks and the Human Costs of Investment Capital in Middle English Romance - Richmond, Andrew M. (Neophilologus, 2015)
Featuring prominently in the romance imagination as terrifying obstacles in the hero’s path, shipwrecks are nevertheless often presented from the salvager’s perspective. Romances abound with knights, clerks, and merchants who obsessively observe nearby beaches and cautiously (yet excitedly) examine the contents of wrecked vessels. Washed ashore, such fruits of maritime disaster delineate medieval English conceptions of seashores as dangerous yet profitable spaces, wherein seaside harvests of (un)natural resources help to stimulate local economic networks. Designations of these shipwrecks as “magical” or “fortuitous” cannot, however, completely elide the source of such wealth in others’ suffering—an unavoidable implication that interrogates contemporary means of attaining investment capital. As such, this paper examines how the littoral space of the seashore is cast as a source of perilous and problematic material bounty in many Middle English romances.
Keywords: Emaré; Geoffrey Chaucer; John Gower; Middle English romance; Shipwrecks; Sir Amadace; dept.eng

Thematic section on premodern digital ecologies - Malcolm, Aylin; Richmond, Andrew (Digital Scholarship in the Humanities, 2026)
Keywords: dept.eng